Bee people - Knappe, David G.; McMahan, Gregg; Jensen, Dawn; Ellis Edits (Firm); Glencross Films; True Mind (Firm); Soundview Media Partners ([Denver, Colo.] : Ellis Edits, Inc. : Glencross Films, 2013)
"For 100 million years, bees have provided sustainability on earth-- yet these glorious pollinators are facing challenges and fading from our planet. Did you know the honeybee is responsible for one third of the items on your dinner plate? "Bee People" raises the bar and provides an in-depth look at the people who are facing the challenge on behalf of the bees, making a difference, and urging everyone to join them on a planet-saving mission! Who are these bee people? What compels them to do what they do? And most importantly, what is the solution they propose? --
Featuring Gregg McMahan, Bill Schlenker, Mike Gallagher, Leslie Ellis, "Tony Bees" Planakis ; narrator, Dawn Jensen.
Cinematography, David G. Knappe ; original music, Kenneth Lampl.
In English; closed-captioned in English.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed May 5, 2017).
Originally released as a motion picture in 2013.
Keywords: Beekeepers; Bee culture; Honeybee -- Effect of human beings on; Nature films; Documentary films; Nonfiction films; Feature films; Internet videos; Streaming video